2018
DOI: 10.1111/mmi.14082
|View full text |Cite
|
Sign up to set email alerts
|

Induced conformational changes activate the peptidoglycan synthase PBP1B

Abstract: SummaryBacteria surround their cytoplasmic membrane with an essential, stress‐bearing peptidoglycan (PG) layer consisting of glycan chains linked by short peptides into a mesh‐like structure. Growing and dividing cells expand their PG layer using inner‐membrane anchored PG synthases, including Penicillin‐binding proteins (PBPs), which participate in dynamic protein complexes to facilitate cell wall growth. In Escherichia coli, and presumably other Gram‐negative bacteria, growth of the mainly single layered PG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 60 publications
(121 reference statements)
7
39
0
Order By: Relevance
“…The presence of the TPase inhibitor ampicillin generally reduced the final FRET level by ~3fold ( Figure 1B, middle panel), indicating that the FRET is mainly a result of TPase reactions. As expected, ampicillin did not prevent the stimulation of PBP1B Ec by LpoB(sol) which accelerated the FRET increase by 10-20 times with or without ampicillin ( Figure 1C), consistent with the previously reported stimulation of both, GTase and TPase activities (Typas et al, 2010, Egan et al, 2018.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…The presence of the TPase inhibitor ampicillin generally reduced the final FRET level by ~3fold ( Figure 1B, middle panel), indicating that the FRET is mainly a result of TPase reactions. As expected, ampicillin did not prevent the stimulation of PBP1B Ec by LpoB(sol) which accelerated the FRET increase by 10-20 times with or without ampicillin ( Figure 1C), consistent with the previously reported stimulation of both, GTase and TPase activities (Typas et al, 2010, Egan et al, 2018.…”
Section: Introductionsupporting
confidence: 91%
“…An elegant recent report (Catherwood et al, 2020) described the use of a coupled D-Ala release assay to determine the kinetic parameters of the TPase activity of PBP1B Ec against different substrates and this study also confirmed the previously reported activation of the TPase of PBP1B by LpoB in the presence of detergents (Egan et al, 2014, Egan et al, 2018, Lupoli et al, 2014. The authors of the recent report (Catherwood et al, 2020) discussed that the LpoB-mediated TPase activation explains the essentiality of LpoB for PBP1B function in the cell.…”
Section: Coupled Reactions In Class a Pbssupporting
confidence: 78%
See 2 more Smart Citations
“…It has been previously hypothesized that the formation of these complexes enables the cell to coordinate and regulate the activities of various synthetic and hydrolytic PG enzymes in a spatiotemporal manner (Höltje, 1993). Within these complexes, the key bifunctional penicillin-binding protein (PBP) PG synthases are activated by cognate outer membrane (OM)-anchored lipoproteins (Paradis-Bleau et al, 2010;Typas et al, 2010Typas et al, , 2012Dorr et al, 2014;Egan et al, 2014Egan et al, , 2018Greene et al, 2018;Moré et al, 2019) and coordinate their action with another, cell constriction-related protein complex (Gray et al, 2015). However, with the exception of the amidases (Uehara et al, 2010;Yang et al, 2012;Peters et al, 2013;Tsang et al, 2017), it is less clear how Gram-negative bacteria control the activities of their repertoire of hydrolases, i.e.…”
Section: Introductionmentioning
confidence: 99%